A numerical interpretation of the chronicle of Huamán Poma de Ayala - Mróz, Marcín (1984)
He retakes one of the themes that has attracted special attention from different scholars following a line of analysis begun by Juan Ossio in his thesis from 1970. The author of this article makes a numerical interpretation of the ages of humanity according to the great Indian chronicler.